Quality of service and satisfaction of care in a family violence module in The province of Cusco - Ancco Choquecondo, Ruth Deysi (2023)
The central objective of the study was to determine the existing relationship of quality of service and satisfaction of care in a specialized module of family violence in Cusco, likewise, it is necessary to specify that it had a basic type of research, with a non-experimental design and level correlational. The population was 484 users, of which a sample of 215 participants was considered, on which a simple random probabilistic sampling was applied, having the survey as a data collection technique, and as instruments a questionnaire for the quality of service and another for the satisfaction of care, validated and submitted to the reliability test. The results show that 84.7% of respondents perceive that there is an adequate quality service provided by the module, likewise 84.7% were pleased with the care provided in the module specialized in violence. Finally, it was concluded with the existence of a direct and moderate relationship between both variables described above, in reference to the fact that it reached a Rho value of 0.405 and a p value of 0.000, thus validating the main hypothesis of the investigation.